Heavy metal exposure, oxidative stress and semen quality: Exploring associations and mediation effects in reproductive-aged men. (April 2020) - He, Yinni; Zou, Lijun; Luo, Wenqi; Yi, Zhiyong; Yang, Pan; Yu, Shuyuan; Liu, Ning; Ji, Jiajia; Guo, Yinsheng; Liu, Peiyi; He, Xinpeng; Lv, Ziquan; et al.
Abstract: Background: Heavy metal exposure induces oxidative stress, which is critical for adverse male reproductive health. Objective: To explore the mediating effect of oxidative stress on the relationship of heavy metal exposure with semen quality. Methods: Urinary levels of three oxidative stress markers, semen quality, and urinary arsenic, cadmium and lead were examined among 1020 men. Multivariate linear regression was applied to explore cross-sectional associations, and the role of oxidative stress as mediators was investigated. Results: Quartiles of metals showed significant dose-dependent relationships with increasing levels of 8-hydroxy-2deoxyguanosine (8-OHdG), 8-iso-prostaglandin F2α (8-isoPGF2α) and 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA). Significant or suggestive associations were also found between urinary 8-OHdG levels and the percentage of normal sperm morphology ( p trend  < 0.001), between urinary 8-isoPGF2α levels and total motility ( p trend  = 0.052), progressive motility ( p trend  = 0.050) respectively. The mediation analysis showed that about 14.59%, 18.06%, 15.35% or 16.49% of the association between arsenic/cadmium exposure and the decreased total motility/progressive motility was mediated by 8-isoPGF2α, respectively. In addition, about 16.47% of the relationship between lead exposure and the decreased percentage of normal sperm morphology was mediated by 8-OHdG. Conclusions: Our findings suggest that higher urinary arsenic, cadmium and lead levels were associated with increased oxidative stress markers, which also related with altered semen quality. 8-isoPGF2α and 8-OHdG might be the possible mediators of the associations between urinary heavy metals and total motility, progressive motility or the proportion of normal sperm morphology. Highlights: Urinary arsenic, cadmium and lead were associated with oxidative stress markers. Urinary 8-OHdG was negatively associated with percentage of normal morphology. Urinary 8-isoPGF2α negatively related with total motility and progressive motility. 8-OHdG mediated association between lead exposure and declined normal morphology. 8-isoPGF2αmediated association between arsenic/cadmium exposure and sperm motility.